2021
DOI: 10.1371/journal.pone.0245584
|View full text |Cite
|
Sign up to set email alerts
|

In silico comparative genomics of SARS-CoV-2 to determine the source and diversity of the pathogen in Bangladesh

Abstract: The COVID19 pandemic caused by SARS-CoV-2 virus has severely affected most countries of the world including Bangladesh. We conducted comparative analysis of publicly available whole-genome sequences of 64 SARS-CoV-2 isolates in Bangladesh and 371 isolates from another 27 countries to predict possible transmission routes of COVID19 to Bangladesh and genomic variations among the viruses. Phylogenetic analysis indicated that the pathogen was imported in Bangladesh from multiple countries. The viruses found in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Notably, few other previous studies although suggest the involvement of the diseases severity with the specific mutation (D614, P323L) in the SARS-CoV-2 genome [ 45 ]. Most interestingly, in two studies by Shishir et al and Garvin et al suggested the involvement of the higher mortality rate in Bangladesh due to the mutation in NSP2, NSP13, and spike protein in the circulating SARS-COV-2 genome in our country, which is in accordance of our study [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, few other previous studies although suggest the involvement of the diseases severity with the specific mutation (D614, P323L) in the SARS-CoV-2 genome [ 45 ]. Most interestingly, in two studies by Shishir et al and Garvin et al suggested the involvement of the higher mortality rate in Bangladesh due to the mutation in NSP2, NSP13, and spike protein in the circulating SARS-COV-2 genome in our country, which is in accordance of our study [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the infection and mortality rates were also disproportionately higher in males than females of Bangladesh. In terms of mortality, it was 79.24% for males and 20.76% for females [ 46 ]. Similar phenomena have also been [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the D614 virus persisted for a longer time in the Delhi region 17 , 19 and also in the South of India, 17 , 20 , 21 , 24 , 27 − 30 while the G614 virus dominated early in the West of India (Gujarat, Maharashtra), 17 , 19 , 25 , 31 and also in the Eastern and Central Indian states, 28 as well as in Bangladesh. 14 , 26 , 32 , 33 Pakistan and Sri Lanka had different waves of virus spread, with an early D614 dominance, but becoming all G614 in June and July 2020. 34 − 36 Importantly, the predominance of the G614 virus was delayed in South India until mid May to June of 2020.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we comprehensively analyzed 791 SARS-CoV-2 complete genome sequences from Bangladesh. Limited molecular analysis of Bangladeshi SARS-CoV-2 was reported previously [ 27 , 28 , 29 ]. We used different bioinformatics approaches to systemically identify the evolutionary matrix, major clades, and lineage designation among the circulated viruses.…”
Section: Discussionmentioning
confidence: 99%